2020
DOI: 10.21272/10.21272/bel.4(3).25-35.2020
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Motivation on Work Efficiency for Both Employers and Employees also During COVID-19 Pandemic: Case Study from Armenia

Abstract: The article summarizes the main arguments and counterarguments within the scientific discussion on motivation and its impact on work efficiency. The main goal of the research is to analyze the impact of motivation on work efficiency for both employees and employers during the COVID-19 pandemic. A systematization of the literary sources on motivation indicates that there are different factors of motivation. Some people are motivated by intrinsic factors, while others by extrinsic. Also, the discussion of some r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 9 publications
2
24
0
1
Order By: Relevance
“…However, research done long before the pandemic and during the pandemic found exciting findings when employees are accustom to the new environment, such as work from home. It is a different working atmosphere, affecting their motivation and tends to changes quickly, and it would disappear when they try to push themself (Purwanto et al, 2020;Tovmasyan & Minasyan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, research done long before the pandemic and during the pandemic found exciting findings when employees are accustom to the new environment, such as work from home. It is a different working atmosphere, affecting their motivation and tends to changes quickly, and it would disappear when they try to push themself (Purwanto et al, 2020;Tovmasyan & Minasyan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Cismas et al (2019) analyze the latest approaches in the economy, including economic and behavioral economics, and consider its relationship with social capital and their impact on education and public health. Undoubtedly, to prevent situations related to mass diseases, in addition to analytical measures, such preventive measures should be taken as the introduction of modern technologies in the business process management system: blockchain (Lopez et al, 2020), remote access technologies (Tovmasyan & Minasyan, 2020), security measures . At the same time, despite a large amount of research in this area, the country's health profile development needs further study and improvement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aside from the health crisis, COVID-19 hit many industries across the country, including the news and communications industry, which is important in times of crisis for bringing authentic and true information [6]. There are some finding in a sphere of industrials performance that was damaged by COVID-19 impact [30], or labour market dynamics that was damaged too [12]. The outbreak became a test and a catalyst for a change in many spheres, such as the service sector [10], sales and hospitality [9], governments and SMEs [29], green technologies and sustainability [16; 31], energy sector [36].…”
Section: Introductionmentioning
confidence: 99%